Development of Christian religious education learning model based on the philosophy of orang basudara life in Maluku - Eklefina Pattinama; Beatrix J.M. Salenussa (KURIOS (Jurnal Teologi dan Pendidikan Agama Kristen), 2022)
Knowledge of the Basudara concept in Maluku is generally understood by adults only. Among young people, the concept of the Basudara is not familiar. The impact of the loss of its concept, that views as a philosophy, among young people in Ambon City, Latta Village, often occurs in brawls between teenagers of different ethics and religions. It is a threat to finding peace and can create new conflicts. Therefore, the teachers need to develop a model of Christian Religious Education for peace based on the philosophy of the Basudara people in Maluku. This study aims to develop a learning model for Christian religious education for peace based on the philosophy of life of the Orang Basudara in Maluku. The research method used is development research using the ADDIE learning model (Analysis-Design-Develop-Implement-Evaluate). The results of this study indicate that the development of the peaceful Christian religious education learning model based on the Orang Basudara philosophy of life in Maluku is needed by Sunday School students. It is learning materials based on local content that can be used as relevant teaching materials. An effective cultural instrument in revitalizing and transforming peace in the context of the Church, which is contextually adapted to the philosophical values of local cultural wisdom in Maluku. Thus, it is concluded that with the teaching materials used, students can apply how to live peacefully side by side in a multicultural context.